World War I : the definitive visual history : from Sarajevo to Versailles - Grant, R. G. (DK Publishing, 2018)
Presents an illustrated history of World War I, including an exploration of its origins, detailed looks at decisive battles, and first-hand accounts of the experiences of civilians and soldiers.